A light in the dark: surviving more than Ted Bundy - Rubin, Kathy Kleiner (Chicago Review Press, 2024)
"In January 1978, I slept in my bed at the Chi Omega sorority house at Florida State University as Ted Bundy stalked nearby. He grabbed an oak log from a stack of firewood, slipped through a back door with a broken padlock, and headed upstairs. He began twisting doorknobs. Room 9 was open, and he quietly and quickly killed one of my sleeping sorority sisters. Across the hall, he found another unlocked door and murdered again. Then, he turned the knob to my bedroom and found it was open. I remember the attack vividly. Bundy bashed me once in the head with the log and then attacked my roommate. He heard me moaning and came to finish me off. He never let his victims live. But he stopped suddenly when a bright light filled the room. He fled the sorority house and the light disappeared. Bundy wasn't my first brush with death, and he wasn't my last. I've long been a survivor"--